2012
DOI: 10.1128/jmbe.v13i1.340
|View full text |Cite
|
Sign up to set email alerts
|

Does the Transition to an Active-Learning Environment for the Introductory Course Reduce Students’ Overall Knowledge of the Various Disciplines in Biology?

Abstract: As biology education is being redesigned toward an interdisciplinary focus and as pedagogical trends move toward active-learning strategies and investigative experiences, a restructuring of the course content for the Introductory Biology course is necessary. The introductory course in biology has typically been a survey of all the biosciences. If the total number of topics covered is reduced, is the students' overall knowledge of biology also reduced? Our introductory course has been substantially modified awa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 14 publications
0
2
0
Order By: Relevance
“…Previous studies have shown that active-learning programs result in greater learning than lecture-based programs (12, 13). The students successfully achieved the goal of finding spices that improve natto flavor.…”
Section: Methodsmentioning
confidence: 97%
“…Previous studies have shown that active-learning programs result in greater learning than lecture-based programs (12, 13). The students successfully achieved the goal of finding spices that improve natto flavor.…”
Section: Methodsmentioning
confidence: 97%
“…While there is a growing body of literature examining faculty innovation in individual classrooms, little research has examined faculty-led efforts to bring about broader institutional change (Lloyd & Eckhardt, 2010;Marbach-Ad et al, 2007;May, Susskind, & Shapiro, 2013;Simurda, 2012). This study contributes to the literature by describing faculty leadership in interdisciplinary change focused on improving community college STEM education.…”
mentioning
confidence: 89%